Landasan Filosofis-Teologis dalam Kurikulum Pendidikan Agama Islam - Nurdiyanto Nurdiyanto; Jamal Jamal; Nurul Azizatul Isnaini; Ferina Yulianti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
In the modern era with all its complexity, a deep understanding of Islamic philosophy and theology becomes very relevant to answer the challenges of globalization, religious pluralism, and social change. From a philosophical-theological basis, the PAI curriculum has high urgency because it is an important basis for forming the understanding and practice of the Islamic religion for Muslim individuals. It is important to note that it not only contributes to the development of a more effective and relevant PAI curriculum but also to the formation of the character and morals of Muslim individuals, which has a major impact on building an ethical and harmonious society. This research aims to analyze the philosophical-theological basis for developing the PAI curriculum and identify its practical implications in the context of Islamic religious education in Indonesia. The approach taken is a qualitative approach, using library research methods with data collection techniques obtained from primary and secondary data. Based on the results of research conducted, it is revealed that the philosophical-theological foundation in the PAI curriculum has a central role in forming meaningful and effective religious education in the Islamic education environment. Islamic philosophy and theology are the main basis for formulating objectives, materials, teaching methods, and values to be conveyed to students in the PAI context, which can help students develop a deeper understanding of Islamic teachings, such as monotheism and the afterlife, as well as values. -moral values that are in accordance with religious teachings, reflect a commitment to maintaining Islamic identity in education, ensuring that religious learning is integrated with consistency in Islamic teachings and values. Thus, the development of a PAI curriculum based on a philosophical-theological foundation contributes to the formation of Muslim students' religious character and commitment, along with maintaining the quality and relevance of Islamic religious education in the educational environment.